Immunohistological detection of Legionella pneumophila in lung sections. Issue 2 (February 1987) - Theaker, J M; Tobin, J O; Jones, S E; Kirkpatrick, P; Vina, M I; Fleming, K A
Abstract : Immunohistology was used for the detection of Legionella pneumophila serogroup I in necropsy tissue. Study of pneumonic lung from the recent Stafford outbreak has shown that this technique has a high sensitivity. A retrospective postmortem examination showed that L pneumophila serogroup 1 was an unusual cause of pneumonia in Oxfordshire during the study period. L pneumophila serogroup 1 can be successfully subgrouped, using a panel of monoclonal antibodies on formalin fixed paraffin embedded sections. Immunohistological methods have a potentially useful role in the diagnosis of Legionellosis at postmortem examination and in the epidemiological investigation of individual cases and outbreaks.